A sociological appraisal of biomedical waste management and its sanitation implications for private clinics in Cotonou town - Nangbe, Florentin (International research journal of management, IT and social sciences, 2018)
Medical activities generate an increasing volume of waste. The management of such produced waste heaps has become a really challenging phenomenon. This research article aims at analyzing the stakes going along with the management of those biomedical waste generated by the private health facilities in Cotonou town. To deliver this objective, qualitative and quantitative research method paradigms have been used for collecting the data, more specifically through desk review, interviews, questionnaires, and direct observation from a sampled population made up of 101 respondents. Following the data collection, processing, analysis, and disaggregation, the results reveal that the strategies used for biomedical waste management in some private health facilities induce some social behaviors responsible for, and causing various pathologies.